(untitled) (Eurasian Research Bulletin, 2022)
The study sought to find out how parental attitude of parents relate to academic achievement of the students in English language. Correlational survey design was adopted for the study. The study was carried out in selected public secondary schools in Uyo Local Government Area of Akwa Ibom State. The population of this study comprised senior secondary two students in Uyo Local Government Area. There are 14 public secondary schools in Uyo Local Government Area and the estimated population of SS2 students was 3162. Simple random sampling technique was used to select eight public secondary schools where 303 SS 2 students were randomly selected for the study. The instrument used in this study for data collection was a questionnaire titled "Students Factors Questionnaire (SFQ)". The instrument was vetted and content validated by the researcher’s supervisor and two lecturers who are experts in language education in the University of Uyo to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.97, and this was high enough to justify the use of the instrument. The data were analyzed using t-test and Pearson Product Moment Correlation statistics analysis. The test for significance was done at 0.05 alpha levels. Parents who show deep interest in the education of their children would motivate them to perform better than parents who only boast about education of their children without practical motivation. And parents who desire greater academic aspiration of their children will supply all the school requisitions and supervise at home what they do. Students whose parents place high premium on their academic pursuit perform better than those students whose parents pay lip services to their education. However, parents who are not educated may not consider it worthwhile to find out the progress of work of their children. Finally, it was concluded that parents with lucrative occupations provide sufficiently for their children academic pursuit. One of the recommendations made in the study was that it is very needful for parents to give advises to their children on matters concerning their education at every time and as well check their homework in order to develop a closer relationship that will positively contribute to academic success.